RANTAI PASOK IKAN LAYANG (Decapterus spp) DI KOTA AMBON - Bethsy Leiwakabessy; Agustinus Tupamahu; Friesland Tuapetel (Universitas Pattimura, 2021)
Marine fish supply chain is an integrated process that combines production until shipping, as well efforts to cut coasts through shipping so as to provide consumers with good service. Eri’s fish landing center is one of the contributors to the stock availability of layang fish in the Ambon. The purpose of the research is to analyze the supply chain layang fish and the level of efficiency. Data were collected by purposive sampling with primary and secondary data from September-December 2019. The results of the study obtained three supply chains with four actors involved in it. Strategies to reduce margins and shorren supply chains by involving key players at high prices, namely papalele and the government at low prices, It is hoped that this alternative is one of the supporting the national fish barn.